Near-field microwave sensor composed of 3D printed antennas and lenses - Wirth, Sebastian G.; Morrow, Ivor L. (IEEE, 2018)
A novel near-field microwave imaging system was designed and fabricated using the three-dimensional (3D) printing technique to manufacture X-band Pyramidal horn antennas and planar graded-index (GRIN) lenses. The flat lens focusing profile is synthesised by varying the refractive index radially in incremental steps that adjust the air-dielectric mixture. The lens is designed for direct attachment to the antenna aperture and transforms spherical waves emanating from antenna phase center into plane radiating waves. Measurement results show the antenna lens system input impedance is ≤ -10 dB, radiation pattern gain is between 10-16 dBi over the 8-12 GHz frequency band and when arrayed for polarimetry sensing has a polarisation cross-talk of ≤ -35 dB. The antenna lens system is suitable for ground penetrating radar applications.
Keywords: Antenna; 3D print manufacture; Microwave imaging; GRIN lens; Polarimetry